IDENTIFIKASI RISIKO STRATEGIS DALAM MENINGKATKAN MUTU PENDIDIKAN (Penelitian di SMP Al-Hasan Kabupaten Bandung) - Aristawati, Nuraini; Hidayat, Wahyu (Department of Islamic Education Management, 2024)
The objectives of this research include: 1) to find out what are the determining factors for strategic risk at Al-Hasan Middle School; 2) to find out what concrete steps have been taken in managing strategic risks at Al-Hasan Middle School; 3) to find out what indicators are used at Al-Hasan Middle School to measure the level of strategic risk in order to improve the quality of education. This research uses qualitative research methods by conducting observations and interviews as the main sources. The results of the research show that there are still many strategic risks identified which of course influence improving the quality of education at Al-Hasan Middle School. Al-Hasan Middle School uses educational report cards as their main indicator in improving the quality of education. Therefore, the author suggests paying more attention to all risks that might occur and increasing skills training for educators so that they can carry out learning better and more effectively in order to improve the quality of education at Al-Hasan Middle School.